Medical interventions and survival by gender of children with trisomy 18. Issue 3 (17th August 2016) - Donovan, Jennifer H.; Krigbaum, Genomary; Bruns, Deborah A.
Abstract : Research has typically shown limited aggressive medical interventions and low survival rates for children with full trisomy 18. Recent studies provide more positive results. This study examined 82 children with full trisomy 18 drawn from the Tracking Rare Incidence Syndromes (TRIS) project database. Children were classified into three groups according to the highest intervention received: "hospice or no intervention" (n = 5, 6.1%), "necessary interventions (enteral feeding, ventilator use)" (n = 46, 56.1%), and "aggressive interventions (surgery)" (n = 31, 37.8%). Seven of 14 male children (50%) and 52 of 68 female children (76.5%) were living at the time of survey completion. Additionally, information about any interventions used during the care of these children was also provided. It was found that three males (37.5%) and 28 females (48.3%) had used hospice care at some point; 12 males (85.7%) and 61 females (89.7%) received enteral feeding at some point; 7 males (58.3%) and 25 females (38.5%) had ventilator; and 7 males (50%) and 33 females (48.5%) underwent some form of surgery. These results suggest improved outcomes when given necessary and aggressive medical interventions. Implications and recommendations for further research are provided. © 2016 Wiley Periodicals, Inc.